Assessing the Factor Structure of the Integrative Hope Scale. (December 2019) - Sharpe, Donald; McElheran, Jesse; Whelton, William J.
While some researchers contend that hope is unidimensional, other researchers regard hope to be multidimensional. Schrank, Woppmann, Sibitz, and Lauber's exploratory factor analysis of their Integrative Hope Scale (IHS) found subscales of Trust, Future Orientation, Social Relations, and Lack of Perspective. However, subsequent articles have utilized only the total IHS score. To resolve this issue, a community sample of 288 participants completed the IHS as well as two measures of hedonic well-being (Positive and Negative Affect Schedule; Temporal Satisfaction With Life Scale), a measure of eudemonic well-being (Measure of Actualization of Potential), and a measure of time orientation (the Zimbardo Time Perspective Inventory). One-factor, four-factor oblique, higher order, and bifactor models were compared through confirmatory factor analysis and interpreted using Omega reliability coefficients. While the poorest model fit was for the one-factor model, little reliable variance was found in subscale scores after controlling for a general hope factor with the exception of the Lack of Perspective factor. IHS total and subscale scores were associated with measures of well-being and time orientation. We suggest researchers continue to focus on using the IHS total score, but also report subscale scores, especially for the Lack of Perspective subscale.